A novel approach on usage of waste sludge from textile dyeing units in paver block manufacturing. (2022) - Kanmani, S.; Anandaraj, S.; Shankar, D.; Remya, P.R.; Vijaymohan, S.; Miruthun, G.; Rakhul, S.B.
Abstract: The viability of using textile sludge as a partial substitute for sand and cement in the construction of paving blocks is being investigated in this study. Along with the sludge, chemicals such as fly ash and lime are applied. The sludge was collected near the dyeing unit and put through a stabilization process to reduce the negative impact on paver blocks. For paver block casting, various trial mixes of M20 grade concrete were created. Compressive strength, split tensile strength, flexural strength, freeze–thaw durability, and water absorption tests were all conducted. Based on the results of the tests, an appropriate sludge concentration has been determined.